CPEB4 Inhibit Cell Proliferation via Upregulating p21 mRNA Stability in Renal Cell Carcinoma - Di, Jiehui; Wang, Hui; Zhao, Zhongjun; Zhao, Guang; Qin, Xiaobing; Han, Zhengxiang; Liu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Cytoplasmic polyadenylation element-binding protein 4 (CPEB4) has been reported to be dysregulated in a variety of cancers and seems to play paradoxical roles in different cancers. However, the functional roles of CPEB4 in Renal cell carcinoma (RCC) are still unclear. This study aims to explore the role and underlying mechanism of CPEB4 in RCC. We found that the relative expression level of CPEB4 is down-regulated in RCC tissues and cell lines, and the low CPEB4 expression is correlated with short overall and disease-free survival of RCC patients. CPEB4 significantly inhibits RCC tumor growth both in vivo and in vitro. CPEB4 exerts an anti-tumor effect by increasing p21 mRNA stability and inducing G1 cell cycle arrest in RCC. Our data revealed that CPEB4 is a tumor suppressor gene that restrains cell cycle progression upstream of p21 in RCC. These findings revealed that CPEB4 may become a promising predictive biomarker for prognosis in patients with RCC.